Macro Economics Perspective on Sustainability Development Goals (SDGs) Indexs in 5 ASEAN Country - Alamsyahbana, Muhammad Isa; Chartady, Rachmad; Bahri, Syaiful; Antania, Livia (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to explore the relationship between macroeconomic factors (GDP, inflation, dollar exchange rate) and the achievement of the Sustainable Development Goals (SDGs) in Indonesia, Singapore, Thailand, the Philippines, and Malaysia. This quantitative research uses secondary data in the form of panel data from the 2017-2022 period. The data collection technique was carried out through secondary data collection, while the data analysis used panel regression with EViews 12 software. The results show that the inflation rate has a significant effect on the achievement of the SDGs, while GDP and the dollar exchange rate do not have a significant relationship. These findings emphasize the importance of controlling inflation in supporting sustainable development and provide insights for policymakers to design more effective development strategies.